Examination of organizational commitment levels of physical education and sports teachers according to various variables (case study of Kutahya province) - Halil Bısgın (Türk Spor ve Egzersiz Dergisi)
This study was conducted to examine the organizational commitment of the physical education and sports teachers, working in the center of Kutahya Province of Turkey, on the basis of their socio-demographic characteristics. One-hundred-and-twenty-six (126) physical education and sports teachers voluntarily participated in the study. Turkish version of the Organizational Commitment Scale developed by Allen and Meyer (1991) was used in this study for data collection. In order to set significant differences (Î±=0.05) in the scope of the study, non-parametric statistical tests of Mann-Whitney U and Kruskall-Wallis tests were conducted according to the results of normality test. In conclusion while affective commitment of the participants' was found to be the highest continuance commitment was found to be the least. Also significant differences emerged between participants' organizational commitment sub dimensions and their gender, age, marital status and professional experience.